Literatur Review: Pengaruh Pengetahuan, Sikap, dan Ketersediaan Fasilitas terhadap Penerapan Keselamatan dan Kesehatan Kerja (K3) pada Petugas Laboratorium - Fitriani Fitriani; Marthia Ikhlasiah (Quantum Wellness : Jurnal Ilmu Kesehatan, 2026)
Laboratories are work environments that contain various physical, chemical, biological, ergonomic, and psychosocial hazards that may lead to occupational accidents and work-related diseases. The implementation of Occupational Health and Safety (OHS) is therefore essential to ensure the safety and well-being of laboratory personnel. Previous studies have shown that the successful implementation of OHS is influenced by several factors, including knowledge, attitudes, and the availability of safety facilities. This study employed a literature review method by examining 10 scientific articles published between 2021 and 2026. The selected articles were identified based on topic relevance, variable suitability, and full-text availability. Data were analyzed descriptively through a synthesis of research findings. Most of the reviewed studies indicated that OHS knowledge was significantly associated with the implementation of safe work practices. Positive attitudes toward occupational safety were found to enhance compliance with the use of personal protective equipment (PPE) and laboratory standard operating procedures (SOPs). Furthermore, the availability of safety facilities, such as PPE, fire extinguishers, first-aid kits, adequate ventilation, evacuation routes, and laboratory SOPs, was shown to support the effective implementation of OHS. Knowledge emerged as the most dominant factor compared to other variables. In conclusion, knowledge, attitudes, and the availability of safety facilities significantly influence the implementation of OHS among laboratory personnel. Strengthening OHS education, fostering a safety culture, and providing adequate safety facilities are necessary to improve the effectiveness of OHS implementation in laboratory settings.